(untitled) (International Journal of Engineering and Computer Science, 2014)
The increase in polarizability of water vapour molecules in the nucleation of water vapour condensation and ice glaciations, result in increase of Gibbs free energy and hence the increase in nucleation rate, but at the same time decrease in relaxation time, the effective polarizability varies nearly inversely as the absolute temperature.